Comparison of INTERGROWTH- 21st and Fenton growth standards to assess size at birth and at discharge in preterm infants in the United Arab Emirates - Cheikh Ismail, L; Mohamad, MN; Ohuma, EO; ElHalik, MS; Dash, SK; Osaili, TM; Hasan, H; Hashim, M; Saleh, ST; Daour, RA; Parker, SR; Ali, HI; et al. (BioMed Central, 2024)
Background: Accurate growth assessment of preterm infants is essential in guiding medical care and suitable nutritional interventions. Currently, different growth references are used across hospitals in the United Arab Emirates (UAE). This study aims to compare the INTERGROWTH-21st standards with Fenton growth references regarding birth size classification and at the time of discharge in a sample of preterm infants in the UAE. Methods: A retrospective single-center evaluation of medical records of infants born < 37 weeks of gestation was conducted using data from 2018 to 2020. Anthropometric measurements (weight, length, and head circumference) were obtained at birth and at the time of discharge, and then converted to percentiles according to the two reference standards. Results: A total of 1537 infants with a median birth gestation of 35.3 weeks, and a median birthweight of 2320 g were included. The rates of SGA, AGA, and LGA at birth were 11.5%, 80.42%, and 9.08% using INTERGROWTH-21st growth charts compared to 9.5%, 83.2%, and 7.3% respectively according to Fenton charts. The findings indicated statistically significant differences between the two growth charts classifying of preterm infants based on weight, length, and head circumference (p < 0.05). For every 5 cases assessed as SGA at discharge according to Fenton charts, only 3 were classified as SGA by INTERGROWTH-21st curves. Conclusions: Differences exist between the two growth charts with only moderate agreement. Thus, there is a need for harmonizing growth assessment standards. Misclassification of these vulnerable infants would affect their in-hospital and post-discharge nutrition and medical care plan.